Personalised antiplatelet therapy in stent thrombosis: observations from the Clopidogrel Resistance in Stent Thrombosis (CREST) registry. Issue 9 (20th April 2012) - Sambu, Nalyaka; Radhakrishnan, Ashwin; Dent, Hazel; Calver, Alison Louise; Corbett, Simon; Gray, Huon; Simpson, Iain A; Curzen, Nick
Abstract : Objective: Previous studies have demonstrated significant heterogeneity in responses to antiplatelet therapy (APT), and high residual platelet reactivity is associated with the risk of ischaemic events, including stent thrombosis (ST). The prevalence of APT hyporesponsiveness in a 'real world' registry of ST patients and the feasibility of personalising APT are reported. Patients and setting: 39 consecutive patients admitted to a single regional cardiothoracic centre with definite ST were prospectively evaluated. Interventions: Response to aspirin and clopidogrel was measured following discharge using short thrombelastography (TEG), a rapid, well validated near patient platelet function test. Treatment modification in hyporesponders comprised an increase in aspirin dose and/or changing clopidogrel to prasugrel or ticagrelor. Short TEG was repeated following treatment modification to ensure an adequate response had been achieved. Results: 12 (31%) patients had an adequate response to both aspirin and clopidogrel, 16 (41%) were hyporesponsive to clopidogrel alone, one (3%) was hyporesponsive to aspirin alone and 10 (26%) were hyporesponsive to both aspirin and clopidogrel. Following treatment modification, an adequate response to aspirin and P2Y12 agent was achieved in 10 (91%) and 22 (85%) patients, respectively. None has presented with a further ST episode. Conclusions: There is a high prevalence of hyporesponsiveness to APT in patients with ST. Improved APT efficacy can be achieved by tailored therapy. Short TEG is a plausible platelet function test that can be used to deliver point of care personalised APT.